PENGARUH PEMBIAYAAN BANK PEMERINTAH DAN BANK SWASTA SEKTOR KONSTRUKSI TERHADAP PERTUMBUHAN PDRB SEKTOR KONSTRUKSI DI KALIMANTAN BARAT TAHUN 2002-2011 - B01109085, Syarifuddin (Jurnal Pembangunan dan Pemerataan, 2013)
The title of this research is "The Effect of Government Bank Financing and Construction Sector Private Bank to the developing of Construction Sector PDRB in West Kalimantan (years 2002-2011)", there are some purposes of this matter such as testing and analyzing the effect of government bank financing and construction sector private bank individually or collectively to the developing of construction sector PDRB in West Kalimantan . The right method to test this relation are the multiple linear regression methods by using the secondary data which taken from Bank Indonesia and the publication of the statistic Centre institution (BPS) in West Kalimantan Province. Based on the results of data processing and calculation, based on a stationary test data has been studied by testing the first difference stationary and cointegrated variables tested are not cointegrated in the long run means that the variable is not cointegrated. As for testing the classical assumptions, models and there is no multicollinearity heterokedastisitas symptoms, but the model contains autokorealasi positive, so to overcome this one with lagrange multiplier test. To the multiple linear regression hypothesis test, the result shows that the probability value of government bank is 0.0389 and the probability value of private bank is 0.0000,that is smaller than alpha (?) = 0:05, then we get result that Government Bank Financing and construction sector Private Bank individually have positive influence and significant to the construction sector PDRB in West Kalimantan. If it seen from R2, the value is 0.913, it shows that the cost has big influence to construction sector PDRB because the R2 value close to 1. Keywords: Financing Government Bank and Private Bank Construction Sector, Construction Sector GDP